(untitled) (CIPEEX, 2025)
Decision-making is crucial for medical residents, who face uncertainties and complexities in their profession. The current study conducted a cross-sectional, analytical, and associative analysis of the decision-making profile and its relationship with sleep quality in 52 residents. Most of the professionals were female and had a high prevalence of poor sleep quality (92%), which can negatively impact mental health, learning, and cognition. The “vigilant” profile, characterized by rational decisions, was the most recurrent in the sample, followed by the “hypervigilant” profile, associated with quick decisions. Poor sleep quality calls into question residents’ self-perception of their decision-making profile, as sleep deprivation can affect the ability to integrate emotion and cognition. The study highlights the need to improve residents’ sleep and to further investigate its relationship with decision-making. Adapting residency programs to the reality of female physicians and promoting the health and well-being of residents are crucial. Despite its limitations, the study contributes to understanding the reality of residents and paves the way for future research on the impacts of sleep on the lives of these professionals.